Implementasi Peraturan Presiden Nomor 28 Tahun 2023 dalam Peningkatan Kesejahteraan Masyarakat Desa Hutan di Kecamatan Mlarak Kabupaten Ponorogo - Maria Yosepin Endah Listyowati; Lilik Prihatin; Muhammad Rofiqul Fadilah; Harjuna Antoni Anan Nugroho (Universitas Ekasakti, 2024)
The economy and welfare of village communities living around state forests is still inadequate. To overcome this social problem, the government is implementing a Social Forestry Program to improve community welfare by utilizing Perhutani land in Mlarak sub-district, Ponorogo district with management rights in environmentally friendly ways to protect Forest sustainability is regulated in Presidential Regulation Number 28 of 2023 concerning Integrated Planning for the Acceleration of Social Forestry Management which is managed by Perum Perhutani as a State-Owned Enterprise. The type of method used is a normative qualitative method where the results of the discussion are social forestry programs covering 5 schemes, namely village forests, community forests, community forests, customary forests and partnership forests which can be utilized by individuals or communities, community groups whose members live around the area. forests and forest farming cooperatives. In this case, the Madiun Forest Management Unit Perhutani (KPH), Ponorogo Regency and the Forest Village Community Institution (LMDH) supported by the Mlarak District Leadership Coordination Forum (Forkopimcam) built an understanding in developing a Social Forestry Business Group (KUPS) in the tourism sector in the District area. Mlarak, With the implementation of the social forestry program, it is an effort to improve the welfare of the people living around the forest through land use for farming, it can also be developed for tourism as well as protecting and maintaining forest sustainability.